Efektivitas dan Evaluasi Konsep SDGs pada Sektor Formal (Studi Kasus: Sekolah Phatnawitya Thailand) - Danendra, Daffa Ibra; Zulkifli, Fadhley Muhammad; Lubis, Deni (Jurnal Pusat Inovasi Masyarakat, 2024)
Education is a fundamental pillar in achieving the Sustainable Development Goals (SDGs), and Thailand, as a Southeast Asian nation, demonstrates its commitment to these goals by starting within formal institutions like schools, guided by national strategies. This community service research aims to assess Thai students' understanding of SDG concepts, identify barriers to comprehensive learning, and propose strategies for sustainable implementation of SDGs in schools. Using a mixed-method approach that includes phenomenology, causal loop diagrams, and fishbone analysis, the research highlights key findings: participatory and contextual educational interventions effectively enhance students' SDG awareness and engagement, while interconnected challenges, such as limited discussions in schools, insufficient teacher training, and inadequate access to information and educational resources, hinder progress. To address these issues, the study recommends improving teacher training and enhancing access to high-quality educational materials as critical strategies to break the cycle of unawareness among students in Yala, Thailand. The overarching conclusion underscores that participatory and contextual education, supported by strong teacher capacity and resource availability, is essential for sustainable success in embedding SDG concepts within formal education.